A Palaeoproterozoic basement beneath the Rangnim Massif revealed by the in situ U–Pb ages and Hf isotopes of xenocrystic zircons from Triassic kimberlites of North Korea. (9th January 2019) - Zhu, Yu-Sheng; Yang, Jin-Hui; Wang, Hao; Wu, Fu-Yuan
Abstract: In situ U–Pb and Hf analyses were used for crustal zircon xenocrysts from Triassic kimberlites exposed in the Rangnim Massif of North Korea to identify components of the basement hidden in the deep crust of the Rangnim Massif and to clarify the crustal evolution of the massif. The U–Pb age spectrum of the zircons has a prominent population at 1.9–1.8 Ga and a lack of Archaean ages. The data indicate that the deep crust and basement beneath the Rangnim Massif are predominantly of Palaeoproterozoic age, consistent with the ages of widely exposed Palaeoproterozoic granitic rocks. In situ zircon Hf isotope data show that most of the Palaeoproterozoic zircon xenocrysts have negative ϵ Hf ( t ) values (−9.7 to +0.7) with an average Hf model age of 2.86 ± 0.02 Ga (2 σ ), which suggests that the Palaeoproterozoic basement was not juvenile but derived from the reworking of Archaean rocks. Considering the existence of Archaean remanent material in the Rangnim Massif and their juvenile features, a strong crustal reworking event is indicated at 1.9–1.8 Ga, during which time the pre-existing Archaean basement was exhausted and replaced by a newly formed Palaeoproterozoic basement. These features suggest that the Rangnim Massif constitutes the eastern extension of the Palaeoproterozoic Liao–Ji Belt of the North China Craton instead of the Archaean Liaonan Block as previously thought. A huge Palaeoproterozoic orogen may exist in the eastern margin of the Sino-Korean Craton.